2019
DOI: 10.1007/s13205-019-1622-y
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting bacterial community structure in artificial pit mud-starter cultures of different qualities: a complex biological mixture for Chinese strong-flavor Baijiu production

Abstract: The complex starter culture for artificial pit mud (APMSC) hosts a wide variety of microbial communities that play a crucial role in Chinese strong-flavor Baijiu production. Based on its organoleptic properties, the quality of APMSC can be divided into normal and inferior quality grades. However, the relationship between the APMSC microbial community and APMSC quality is poorly understood. In this study, the bacterial community structure in normal and inferior APMSC derived from two different production batche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Finally, the mixture was covered with polyester film and incubated at ambient temperature (20 to 34°C, with an average of 24°C) for 34 days (from 28 July 2017 to 30 August 2017). The starter culture preparation is described in detail in our previous study (45).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the mixture was covered with polyester film and incubated at ambient temperature (20 to 34°C, with an average of 24°C) for 34 days (from 28 July 2017 to 30 August 2017). The starter culture preparation is described in detail in our previous study (45).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the large number of C. kluyveri and increased share of Clostridium cluster IV might lead to the increased levels of ethyl caproate in Baijiu from an aged cellar. The content of ethyl caproate was reported to be positively correlated with Chinese strong flavour Baijiu quality (28). Thirdly, since Petrimonas (5), Sedimentibacte (5) and Syntrophomonas (32) produce acetic acid, the reduced share of Petrimonas, Sedimentibacter, and Syntrophomonas may result in decreased acetic acid and ethyl acetate from the aged cellar, while both compounds may increase in Baijiu from the young cellar (33).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with previous work , the results using the two methods (DDGE and high‐throughput sequencing) are mutually supportive. Comparison of the results indicated that the microorganisms detected by DGGE were recovered by high‐throughput sequencing with exception of Anaerolineaceae and Planctomycete.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that Caproiciproducens could produce caproic acid (Kim et al, 2015), and that Clostridium sensu stricto, as one kind of strictly anaerobic bacteria, was regarded as the true Clostridium (Chai et al, 2019). It could ferment cellulosic-based biomass and sugar to form butyric acid and eventually to produce ethyl caproate (Barker et al, 1945;Liu et al, 2019). Excessive levels of ethyl lactate might make the liquor harmony worse, while ethyl caproate is recognized as a key component favorably influencing the flavor of CSFL (Tao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%